Forest insects and climate change: long-term trends in herbivore damage - Klapwijk, Maartje J (Blackwell Publishing Ltd, 2013)
Long-term data sets, covering several decades, could help to reveal the effects of observed climate change on herbivore damage to plants. However, sufficiently long time series in ecology are scarce. The research presented here analyzes a long-term data set collected by the Hungarian Forest Research Institute over the period 1961–2009. The number of hectares with visible defoliation was estimated and documented for several forest insect pest species. This resulted in a unique time series that provides us with the opportunity to compare insect damage trends with trends in weather patterns. Data were analyzed for six lepidopteran species: Thaumetopoea processionea, Tortrix viridana, Rhyacionia buoliana, Malacosoma neustria, Euproctis chrysorrhoea, and Lymantria dispar. All these species exhibit outbreak dynamics in Hungary. Five of these species prefer deciduous tree species as their host plants, whereas R. buoliana is a specialist on Pinus spp. The data were analyzed using general linear models and generalized least squares regression in relation to mean monthly temperature and precipitation. Temperature increased considerably, especially over the last 25 years (+1.6°C), whereas precipitation exhibited no trend over the period. No change in weather variability over time was observed. There was increased damage caused by two species on deciduous trees. The area of damage attributed to R. buoliana decreased over the study period. There was no evidence of increased variability in damage. We conclude that species exhibiting a trend toward outbreak-level damage over a greater geographical area may be positively affected by changes in weather conditions coinciding with important life stages. Strong associations between the geographical extent of severe damage and monthly temperature and precipitation are difficult to confirm, studying the life-history traits of species could help to increase understanding of responses to climate change.